Genetic validation of a TSC2 immunohistochemistry assay in TSC/mTOR-pathway altered renal tumors - Akbari, Amir; Villanueva, Clarence Rachel; Hes, Ondrej; Williamson, Sean R; Kandukuri, Shivani; Sharma, Shivani; Aditi, Aggarwal; Pivovarcikova, Kristyna; Argani, Pedram; Mohanty, Sambit K; Asrani, Kaushal; Lotan, Tamara L (Human pathology, 2024)
Pathogenic mutations in the genes associated with tuberous sclerosis complex (TSC)/mTOR pathway are linked to histologically diverse renal cell neoplasms, including eosinophilic solid and cystic renal cell carcinoma (ESC RCC), low grade oncocytic tumor (LOT), eosinophilic vacuolated tumor (EVT), and xanthomatous giant cell renal cell carcinoma (XGC RCC). Here, we validate a TSC2 immunohistochemistry (IHC) assay by comparison to genomic data in these neoplasms. Automated TSC2 IHC was performed on formalin-fixed paraffin embedded (FFPE) tissues from 38 genetically-confirmed TSC/mTOR-associated renal tumors (6 ESCs, 16 EVTs, 13 LOTs, 2 XGC and 1 clear cell RCC) and visually scored in a semi-dichotomous fashion compared to internal control tissue. The positive predictive value (PPV) of TSC2 protein loss for underlying pathogenic mutation in TSC2 was 92% (11/12), while the negative predictive value (NPV) of intact TSC2 by IHC for lack of underlying pathogenic mutation in TSC2 was 81% (21/26). Intact TSC2 by IHC was 95% (21/22) specific for absence of underlying pathogenic TSC2 mutation. All the cases lacking TSC2 mutation with intact TSC2 protein had an underlying mutation in TSC1, MTOR or PIK3CA. Loss of TSC2 was 77% (10/13) sensitive for underlying TSC2 truncation mutations and 33% (1/3) sensitive for underlying TSC2 missense mutations. Overall, 73% (8/11) tumors with TSC2 IHC loss and underlying pathogenic alterations in TSC2 showed heterogeneous protein loss, with rare interspersed positively staining tumor cells. These data support TSC2 IHC as a potentially useful assay for the diagnostic workup of renal tumors suspected to belong to the TSC/mTOR-associated subgroups.
Keywords: Tuberous Sclerosis; signální transdukce; Reproducibility of Results; tuberin; Carcinoma, Renal Cell; reprodukovatelnost výsledků; lidé; Predictive Value of Tests; imunohistochemie; DNA Mutational Analysis; Middle Aged; mužské pohlaví; Signal Transduction; prediktivní hodnota testů; mutace; Genetic validation; karcinom z renálních buněk; Adult; Renal cell carcinoma; mutační analýza DNA; Kidney Neoplasms; TSC2; Tuberous Sclerosis Complex 2 Protein; Biomarkers, Tumor; Immunohistochemistry; ženské pohlaví; nádorové supresorové proteiny; nádorové biomarkery; Mutation; Humans; TOR Serine-Threonine Kinases; TOR serin-threoninkinasy; Tumor Suppressor Proteins; lidé středního věku; dospělí; Female; tuberózní skleróza; nádory ledvin; Male